EP 58. Examining the right dorsal premotor mosaic: A connectivity-based parcellation approach. Issue 9 (September 2016) - Genon, S.; Müller, V.; Cieslik, E.; Hoffstaedter, F.; Langner, R.; Reid, A.; Grefkes, C.; Eickhoff, S.
Abstract : Little is known about how several functions are organized or how putative subregions are coupled with wider brain networks in the human right PMd. To address these issues, we performed connectivity-based parcellation (CBP) based on PMd voxels' coactivations yielded by meta-analytic connectivity modeling (MACM). We additionally search for a similar cluster solution with CBP based on resting-state functional connectivity (RSFC) and probabilistic diffusion tractography. MACM and RSFC assessed FC of the MACM–CBP-derived subregions while functional characterization revealed their behavioral associations. This procedure showed that the right PMd could be divided into five distinct clusters highlighting a cognitive-motor gradient along a rostro-caudal axis including a rostral cluster functionally interacting with prefrontal cortex in supporting high-level cognitive processes and a caudal cluster closely integrated with the motor system. MACM–CBP also revealed a ventral cluster, whose functional profile fits the concept of an eye field, and a dorsal cluster, preferentially hand-related and connected to both cognitive and motor regions. Finally, MACM–CBP yielded a central cluster showing a mixed behavioral profile and FC to parietal regions of the dorsal attention network. Thus, our results showed that the right PMd may be considered as a functional mosaic formed by five subregions.